MALE URINARY INCONTINENCE AND THE DIGITAL TECHNOLOGY: EVALUATION OF MOBILE APPLICATIONS AVAILABLE FOR DOWNLOAD - Machado, Adriana Ferreira; Estevam, Fabrícia Eduarda Baia; Izidoro, Lívia Cristina de Rezende; Oliveira, Hugo Miranda de; Anjos, Filipe Maciel de Souza dos; Carvalho, Sérgio Teixeira de; Mata, Luciana Regina Ferreira da (Cogitare Enfermagem, 2022)
Objective: to evaluate the suitability and usefulness of mobile apps aimed at urinary incontinence rehabilitation in the male population. Method: descriptive study, carried out with apps directed to the rehabilitation of male urinary incontinence. The apps were obtained from the Play Store and App Store. The search was conducted between May 3 and 10, 2021, in Minas Gerais, Brazil. The terms "urinary incontinence", "incontinencia urinaria", "urinary incontinence", and "Kegel" were used for selection. The applications were described and evaluated as established in the Applications Scoring System items. Results: Twenty-two apps were selected. Three were specific for men; three addressed exercises for pelvic muscle strengthening and voiding diary simultaneously; and five were compatible with both online stores. Conclusion: most of the available apps have limited functionality and information about male urinary incontinence. This study is expected to contribute to the development of more comprehensive and appropriate software for the male urinary incontinent population.